Ground rolling delays apical development and reduces frost injury in early-sown spring wheat. (2nd October 2022) - Mizumoto, Akina; Tanio, Masahiko; Watanabe, Kazuhiro; Nakazono, Kou; Uchino, Akira; Azuma, Tetsushi
ABSTRACT: Frost injury is a concern in early-sown spring wheat ( Triticum aestivum ) in the Tokai region of Japan. To assess the efficacy of ground rolling as a technique for avoiding frost injury, we investigated its effects on the apical development and yield of 'Ayahikari' spring wheat. In both 2018–19 and 2019–20, rolling delayed spikelet initiation by 4–5 days, the start of internode elongation by 5–12 days, and jointing by 3–9 days, but did not affect the apical development rate, which depended on the thermal time. Ground rolling prevented frost injury in 2018–19 but not in 2019–20, probably because the warmer-than-average winter promoted earlier jointing, and so plants were exposed to later low temperatures in February. These results suggest that ground rolling is an effective method for avoiding frost injury in spring wheat during cold winters. GRAPHICAL ABSTRACT: uf0001